PROGRAMMABLE DYNAMIC SIMULATOR OF STATIONARY PLASMA THRUSTER - Dmitry Demchenko; Andrey Vlasenko; Egor Shilov; Ivan Popov; Ruslan Akhmetzhanov (Proceedings on Engineering Sciences)
The paper presents the results of development of microelectronic simulator of high-pulse dual-mode correction unit. The unit makes it possible to optimize the process of testing power processing units of electric propulsion, to work through the interaction of onboard spacecraft systems with power processing unit, and to investigate the influence of transients occurring in the propulsion system on the stability of the spacecraft power circuits, thereby increasing the reliability of spacecraft as a whole.